Pediatric infection with the Omicron variant increases the risks of febrile seizures among COVID-19 infected children - Mohamed, Zakaria Ahmed; Tang, Chunjiao; Thokerunga, Erick; Deng, Youping; Fan, Jingyi (Frontiers in Pediatrics, 2023)
Background: The Omicron variant of the severe acute respiratory syndrome coronavirus 2 (SARS -CoV -2) is less likely to cause severe disease in children than the other variants but has become an increasing cause of febrile seizures (FS) among children. In this case-control study, we aimed to examine the risk factors associated with FS in children infected with the covid-19 Omicron variant and related treatment modalities. Methods: This retrospective case-control study includes 113 subjects infected with the covid-19 Omicron variant, grouped into 45 cases (those with FS) and 68 controls (those without FS). Data on clinical features, laboratory parameters, and treatment modalities were collected and analyzed. Results: Approximately 5.74 % of covid-19 infected children developed Covid-19-associated FS. Children with covid-19 and high body temperatures [RR 1.474; (95% CI: 1.196 -1.818), p<0.001], previous history of FS [RR 1.421; (95% CI: 1.088 -1.855), p=0.010], high procalcitonin levels [RR 1.140; (95% CI: 1.043 -1.246), p=0.048] and high neutrophil counts [RR 1.015; (95% CI: 1.000 -1.029), p=0.048] were more likely to experience FS than the controls.In contrast, children with COVID-19 and low eosinophil counts, low hemoglobin levels, and cough had a lower risk of developing FS [RR 0.494; (95% CI: 0.311 -0.783), p=0.003], [RR 0.979; (95% CI: 0.959 -0.999), p=0.044]; and [RR 0.473 (95% CI 0.252-0.890), p=0.020]; respectively. Children with FS received more anti-flu medications than those without.Conclusion: A significant increase in FS was observed in children with Omicron SARS-CoV-2 infection. A higher body temperature, a history of FS, a higher procalcitonin level, and a high neutrophil count were all associated with an increased risk of FS in children with Covid-19. The risk of developing FS was lower in children with covid-19 and low eosinophil counts and hemoglobin levels than in those without.